Clinical features of eczema and dermatitis in the elderly: A cross-sectional study in mainland China. (8th January 2022) - Wang, Xin; Li, Lin-Feng
Purpose : The clinical features of eczema and dermatitis in the elderly have not been fully studied. To investigate the proportion and clinical features of geriatric eczema patients in mainland China. Patients and methods : A multicenter cross-sectional study conducted in outpatients with eczema from 39 tertiary hospitals in 15 provinces. Results : 1128 elderly patients (12.88%) had eczema and dermatitis. The mean age of those was 68.2 ± 6.8 years (range, 60–90 years) with a median course of 5.5 ± 8.9 years, which is much longer than that of non-geriatric patients (2.6 ± 4.1 years, p < 0.001). Compared to non-geriatric patients, more patients involved in extremities (76.2% vs 61.5%, p < 0.001) and trunk (37.2% vs 26.4%, p < 0.001), but less in head and neck (18.3% vs 30.4%, p < 0.001; 25.3% vs 20.6%, p < 0.001). 13.4% of eczema and dermatitis in the elderly was widespread, which is much higher than that of 8% in non-geriatric group (13.4% vs 8%, p < 0.001). 22.9% of geriatric eczema patients reported severe itching, which is much higher than that of 14% in counterparts (22.9% vs 14%, p < 0.001). A positive correlation was observed between age and severe itching (Spearman's rank correlation test, p < 0.001). More geriatric patients had xerosis (39.6% vs 30.4%, p < 0.001) and more lichenification was found (25.6% vs 13.3%, p < 0.001). Conclusion : More than 10% of eczema occurs in the elderly patients. Longer disease duration, more severe itching, more extremities and trunk involvement, and prone to widespread, xerosis, and lichenification make it a special entity which should be studied further.